Treatment of Industrial Oily Effluent Using a Biossurfactant from Pseudomonas Cepacia Cct6659 as an Alternative Collector in a Bench Scale-induced Saturation Tower - Aldemar Antonio Pedrosa Campello Filho; Yslla Emannuelly Da Silva Faccioli; Charles Bronzo Barbosa Farias; Pedro Pinto Ferreira Brasileiro; Leonardo Bandeira Dos Santos; Valdemir Alexandre Dos Santos; Rita De Cássia Freire Soares Da Silva; Leonie Asfora Sarubbo (Chemical Engineering Transactions, 2020)
The increase in activities related to the oil and electric power sector are mainly responsible for the production of oily waters and their disposal, requiring treatment strategies and separation of these wastes. For the treatment of oily water, flotation technology employing air microbubbles for contaminant saturation can be employed efficiently. Chemical surfactants are applied as collectors for separation of suspended oil particles. Biosurfactants biodegradable and non-toxic, stand out as alternative collectors in the treatment of industrial effluents replacing synthetic and toxic surfactants. The present work aims to present an efficient solution through the of an innovative induced-air microbubble flotation prototype configured in a Stage Induced Saturation Tower (IST), in bench scale. This technology emerges as a more efficient and economical solution for the treatment of industrial wastewater using biosurfactants as collectors because they are biodegradable and have reduced toxicity. In this sense, the potential of the biosurfactant produced by Pseudomonas cepacia CCT6659 as an alternative collector in the treatment of an oily effluent from a thermoelectric plant was evaluated. Comparative tests were performed using the proposed biosurfactant, a cationic polymer, a synthetic surfactant (sodium dodecyl sulfate) and a commercial rhamnolipid classified biosurfactant of Pseudomonas aeruginosa. The tests were performed in the new system after homogenization between surfactant / effluent. The sample was fed at the top of the Tower and successively interacted with upward streams of air microbubbles at different stages. Samples of treated effluent were collected to evaluate the percentage of oil removal by spectrophotometry. The most significant results of the surfactant activities of the biosurfactant produced were: surface tension of 26 mN / m, emulsification capacity of 98.72% and dispersion action of approximately 86.00%. The IST system, with the action of microbubbles alone, achieved a 75.00% oil removal. The high efficiency of water / oil separation by P. cepacia biosurfactant compared to the collectors was proven from the removal of 97.49% of oil contained in the industrial effluent. Therefore, the potential of this surfactant agent as an alternative collector in an induced saturation flotation system proved helps to reduce the environmental impacts caused by industrial plants.